Konsep Pendidikan Kalbu: Telaah Pemikiran Al-Ghazali tentang Hati sebagai Pusat Pendidikan Moral - Ivan Maulana Yusuf; Muhammad Arif Syihabuddin (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This article examines the concept of heart education in Imam Al-Ghazali's thought, placing the heart (qalb) as the center of human moral and spiritual development. This research is motivated by the tendency of modern education to emphasize cognitive aspects and academic achievement, while often marginalizing moral and spiritual dimensions. This condition has implications for the emergence of various moral problems and character crises in society, particularly among the younger generation. This study uses a qualitative approach with a literature study method, which examines Al-Ghazali's main works, such as Ihya' Ulum al-Din, Mizan al-'Amal, and Kimya' al-Sa'adah, as well as supporting literature from relevant scientific books and journals. The analysis is carried out descriptively and analytically to reveal the nature of the heart, its spiritual function, the process of purifying the soul, the purpose of heart education, and the method of moral development offered by Al-Ghazali. The results of the study show that heart education in Al-Ghazali's perspective is a holistic educational system that is not only oriented towards the formation of external behavior, but also emphasizes the transformation of the human heart. Education of the heart encompasses the integration of cognitive, ethical, emotional, and spiritual aspects through the process of tazkiyatun nafs (self-control), controlling desires, cultivating noble morals, and strengthening spirituality. The educational methods used, such as role models, habituation, advice, self-reflection, and self-examination, are considered relevant for application in the context of modern education. Thus, Al-Ghazali's thoughts on the education of the heart can serve as a conceptual foundation for developing more comprehensive character education to address the moral crisis and character degradation in the era of globalization. Keywords: Heart Education, Al-Ghazali, Heart, Morals, Character